Reducing fear of water and aquaphobia through 360 degree video use? - Roche, Lionel; Cunningham, Ian; Rolland, Cathy; Fayaubost, Régis; Maire, Sébastien (Frontiers in Education, 2022)
Drowning is a major public health problem. In 2019, the United Nations Educational, Scientific and Cultural Organisation (UNESCO) estimated 236,000 people died from drowning and drowning is the third leading cause of unintentional injury death. Learning to swim requires limited fear of water. With our exploratory study, we try to identify potential interest of 360° video use for reducing fear and apprehension that underpin aquaphobia. The study is qualitative and positioned in the theoretical lens of the Course of Action research approach (Theureau, 2010) used in cognitive anthropology and is part of the enaction paradigm and embodied cognition perspective. This exploratory study was realized with two students from a group of students aged 11-12 years. All participants were non-swimmers. and had a reluctance to enter the water (i.e., a refusal and/or fear of immersion, immersion only of part of the face or the body). Three main results of the study can be underlined. First, the use of 360° video viewed in a HMD led students to live an original corporeal immersive experience ; a kind of immersion in the pool but experienced outside the pool. Second, students felt a strong emotional engagement between anxiety and curiosity from exploring the aquatic environment. Third, during the viewing situation, students developed and acquired accurate perceptive cues and knowledge related to the aquatic environment.